The grapevine VviPrx31 peroxidase as a candidate gene involved in anthocyanin degradation in ripening berries under high temperature - Movahed, Nooshin; Pastore, Chiara; Cellini, Antonio; Allegro, Gianluca; Valentini, Gabriele; Zenoni, Sara; Cavallini, Erika; D’Incà, Erica; Tornielli, Giovanni Battista; Filippetti, Ilaria (Journal of plant research, 2016)
Anthocyanin levels decline in some red grape berry varieties ripened under high-temperature conditions, but the underlying mechanism is not yet clear. Here we studied the effects of two different temperature regimes, representing actual Sangiovese ( Vitis vinifera L.) viticulture regions, on the accumulation of mRNAs and enzymes controlling berry skin anthocyanins. Potted uniform plants of Sangiovese were kept from veraison to harvest, in two plastic greenhouses with different temperature conditions. The low temperature (LT) conditions featured average and maximum daily air temperatures of 20 and 29 °C, respectively, whereas the corresponding high temperature (HT) conditions were 22 and 36 °C, respectively. The anthocyanin concentration at harvest was much lower in HT berries than LT berries although their profile was similar under both conditions. Under HT conditions, the biosynthesis of anthocyanins was suppressed at both the transcriptional and enzymatic levels, but peroxidase activity was higher. This suggests that the low anthocyanin content of HT berries reflects the combined impact of reduced biosynthesis and increased degradation, particularly the direct role of peroxidases in anthocyanin catabolism. Overexpression of VviPrx31 decreased anthocyanin contents in Petunia hybrida petals under heat stress condition. These data suggest that high temperature can stimulate peroxidase activity thus anthocyanin degradation in ripening grape berries.